Using expressive arts to work with the mind, body and emotions : theory and practice - Pearson, Mark, 1950- (Jessica Kingsley Publishers, 2009)
Using Expressive Arts to Work with Mind, Body and Emotions combines theory, research and activities to produce practical suggestions for enhancing client participation in the therapy process. It surveys the literature on art therapy; somatic approaches; emotion-activating models; use of music, writing and dreamwork; and the implications of the new findings in neuroscience. The book includes step-by-step instructions for implementing expressive therapies techniques, and contains a wide range of experiential activities that integrate playful yet powerful tools that work in harmony with the clien.